Exploring the Role of Internal Communication in Managing Employees’ Emotions During Digital Strategy Implementation in the Banking Sector in Bangladesh - Jahan, Rifat (My University, 2025)
The adoption of digital strategy is now one of the strategic goals in most of the organizations, including the banking sector in developing countries. The digital strategy implementation process is not easy for all companies. The success depends on many aspects. Among them, employees’ emotions are very important and influence the process of digital strategy imple-mentation digital. Moreover, emotional preparedness of frontline employees depends on how well they are informed or communicated with during digital strategy execution. This study investigates the significant role of internal communication during digital strategy implementation in the banking sector in Bangladesh. This study applies a qualitative case study methodology. The case company is a private commercial bank, and it focuses mainly on two departments, which have recently implemented significant digital strategies. For data collection, this study conducted semi-structured interviews where the participants were managers and their team members. It was also supported by secondary data online, public resources, and the company’s official website. The analysis integrated thematic analy-sis and content analysis through an abductive approach. Three main themes were developed by thematic analysis, which focused on how transparent communication, training sessions, and leadership communication generated reliability and confidence of employees in digital strategy implementation process. The results show that supportive, clear, rewarding, and reciprocating internal communication assists workers in shifting their emotions from anxiety to engagement. This study pro-vides useful insights on addressing employee emotions in the process of digital strategy im-plementation and specific recommendations for the banking sector in hierarchical settings like Bangladesh.
Keywords: internal communication; banking sector; bangladeshilaiset; employees; emotions; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development